Два новые для фауны Советского Союза циклопа (Crustacca, Cyclopidae) - Монченко, В.И. (Вестник зоологии, 1976)
Diacyclops languidus belgicus Kiefer and D. L. disjunctus (Thallw.) are described and figured. Both cyclops are found by the author in different parts of the Ukraini- an, Byelorussian SSR and the later also in Poland, mainly in subterranean waters (spring, well), but also in opened water bodies (moss marshs, temporary pools, etc). The questions of speciation in these taxons are discussed.